Resting heart rate and incident venous thromboembolism: the Multi-Ethnic Study of Atherosclerosis - Awotoye, Josephine (Open Heart, 2020)
OBJECTIVE: Venous thromboembolism (VTE) is associated with significant morbidity and mortality. Resting heart rate (RHR), which may be modifiable through lifestyle changes, has been shown to be associated with cardiovascular disease risk and with inflammatory markers that have been predictive of VTE incidence. METHODS: We examined whether RHR is also associated with VTE incidence independent of these risk factors. We studied 6479 Multi-Ethnic Study of Atherosclerosis participants free from clinical VTE at baseline who had baseline RHR ascertained by 12-lead ECG. VTE events were recorded from hospital records and death certificates using International Classification of Diseases (ICD)-9 and ICD-10 codes. We categorised RHR as <60, 60–69, 70–79 and ≥80 bpm. We used Cox hazard models to determine the association of incident VTE by RHR. RESULTS: Participants had mean (SD) age of 62 (10) years and RHR of 63 (10) bpm. RHR was cross-sectionally correlated with multiple inflammatory and coagulation factors. There were 236 VTE cases after a median follow-up of 14 years. Compared with those with RHR<60 bpm, the HR (95% CI) for incident VTE for RHR≥80 bpm was 2.08 (1.31 to 3.30), after adjusting for demographics, physical activity, smoking, diabetes and use of atrioventricular (AV)-nodal blockers, aspirin and anticoagulants, and remained significant after further adjustment for inflammatory markers (2.05 (1.29 to 3.26)). Results were similar after excluding those taking AV-nodal blocker medications. There was no effect modification of these associations by sex or age. CONCLUSION: Elevated RHR was positively associated with VTE incidence after a median of 14 years; this association was independent of several traditional VTE and inflammatory markers.